(The Reconstruction of) Lucius Annaeus Cornutus’ Commentary on Vergil - László Takács (Aitia, 2018)
According to ancient testimonies the Stoic philosopher Lucius Annaeus Cornutus published one or two works on Vergil. Some fragments of these work(s) are still accessible today. Thus some scholars based their attempts to give a general evaluation of Cornutus as a philologist on them. As it is obvious that the late ancient commentaries saved more fragments written by Cornutus without mentioning his name, in this study I am trying to associate a greater number of the fragments to Cornutus’ lost work(s) on Vergil, and to re-evaluate the Stoic philosopher as a literary critic.